1997
DOI: 10.1016/s0928-8244(97)00093-x
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma salivarium induces interleukin-6 and interleukin-8 in human gingival fibroblasts

Abstract: Analysis by an enzyme-linked immunosorbent assay for cytokines indicated that whole cells, intracellular materials and cell membranes of Mycoplasma salivarium induced interleukin-6 and interleukin-8 in a human gingival fibroblast cell line, Gin-1 cells. This was confirmed by reverse transcription-polymerase chain reaction analysis of mRNAs of these cytokines. Studies with inhibitors of second-messenger pathway indicated that a protein kinase C-dependent pathway was involved in the expression of the activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 22 publications
(29 reference statements)
1
48
0
Order By: Relevance
“…Wall-less mycoplasmas lack them except for lipoproteins. Lipoproteins of some mycoplasma species are known to activate monocytes/macrophages, lymphocytes, or fibroblasts (2,3). This study also demonstrated that membrane-bound lipoproteins of M. salivarium possessed the activity to activate HGF or THP-1 cells.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Wall-less mycoplasmas lack them except for lipoproteins. Lipoproteins of some mycoplasma species are known to activate monocytes/macrophages, lymphocytes, or fibroblasts (2,3). This study also demonstrated that membrane-bound lipoproteins of M. salivarium possessed the activity to activate HGF or THP-1 cells.…”
Section: Discussionsupporting
confidence: 55%
“…salivarium cells were treated with Triton X-114 to extract lipoproteins (TXLP) according to the method described previously (3). TXLPs in the Triton X-114 phase were precipitated by methanol and used for stimulation after being suspended in sterile PBS by light sonication.…”
Section: Preparation Of Lipoproteins By the Triton X-114 Phase Separamentioning
confidence: 99%
See 1 more Smart Citation
“…Mycoplasmal cells were treated with Triton X-114 to extract membrane lipoproteins according to the method described previously (27). The cell suspension (0.9 ml) was mixed with 0.1 ml of 20% (v/v) Triton X-114 working stock solution.…”
Section: Methodsmentioning
confidence: 99%
“…Mycoplasmal lipoproteins activate monocytes/ macrophages and fibroblasts to produce inflammatory cytokines (23,27). There is a possibility that cytokines are involved in the cytotoxicity of LPsal and LPfer.…”
Section: Effects Of Mabs To Tnf-α Fasl and Il-1β On The Cytotoxicitmentioning
confidence: 99%